Systems Biology of Cancer Metastasis - Suhail, Yasir; Cain, Margo P.; Vanaja, Kiran; Kurywchak, Paul A.; Levchenko, Andre; Kalluri, Raghu; Kshitiz (Cell systems, 2019)
Cancer metastasis is no longer viewed as a linear cascade of events but rather as a series of concurrent, partially overlapping processes, as successfully metastasizing cells assume new phenotypes while jettisoning older behaviors. The lack of a systemic understanding of this complex phenomenon has limited progress in developing treatments for metastatic disease. Because metastasis has traditionally been investigated in distinct physiological compartments, the integration of these complex and interlinked aspects remains a challenge for both systems-level experimental and computational modeling of metastasis. Here, we present some of the current perspectives on the complexity of cancer metastasis, the multiscale nature of its progression, and a systems-level view of the processes underlying the invasive spread of cancer cells. We also highlight the gaps in our current understanding of cancer metastasis as well as insights emerging from interdisciplinary systems biology approaches to understand this complex phenomenon. Cancer metastasis is a complex disease, arising from a growing tumor from which cells escape to other parts of the body. For long, cancer metastasis was considered as a combination of steps, which were studied separately, limiting our understanding of this complex disease. Here, we present the new developments and our perspective on how the new systems biology approach is changing our view of cancer metastasis as an integrated multiscale phenomenon comprising interlinked parts that allow tumors to metastasize.